(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article discusses the importance of emotions in human life, their types and psychological characteristics. It also analyzes the impact of emotions on a person’s mental state, communication and daily activities. The article discusses the impact of positive and negative emotions on human behavior and reveals the importance of managing emotions. This article serves to study the role of emotions in human development.